ChemInform Abstract: Asymmetric Construction of Spirooxindoles by Organocatalytic Multicomponent Reactions Using Diazooxindoles. Issue 48 (December 2015) - Wu, Ming‐Yue; He, Wei‐Wei; Liu, Xin‐Yuan; Tan, Bin
Abstract: This highly diastereo‐ and enantioselective method to give various spirooxindoles is realized using a newly developed hydrogen‐bond catalyst, for the first time.